The G protein‐coupled receptor ligand apelin‐13 ameliorates skeletal muscle atrophy induced by chronic kidney disease. Issue 1 (23rd December 2022) - Enoki, Yuki; Nagai, Tomoya; Hamamura, Yuna; Osa, Sumika; Nakamura, Hideaki; Taguchi, Kazuaki; Watanabe, Hiroshi; Maruyama, Toru; Matsumoto, Kazuaki
Abstract: Background: Targeting of the apelin–apelin receptor (Apj) system may serve as a useful therapeutic intervention for the management of chronic kidney disease (CKD)‐induced skeletal muscle atrophy. We investigated the roles and efficacy of the apelin–Apj system in CKD‐induced skeletal muscle atrophy. Methods: The 5/6‐nephrectomized mice were used as CKD models. AST‐120, a charcoal adsorbent of uraemic toxins (8 w/w% in diet), or apelin (1 μmol/kg) was administered to CKD mice to investigate the mechanism and therapeutic potential of apelin on CKD‐induced skeletal muscle atrophy. The effect of indoxyl sulfate, a uraemic toxin, or apelin on skeletal muscle atrophy was evaluated using mouse myoblast cells (C2C12 cells) in vitro. Results: Skeletal muscle atrophy developed over time following nephrectomy at 12 weeks, as confirmed by a significant increase of atrogin‐1 and myostatin mRNA expression in the gastrocnemius (GA) muscle and a decrease of lower limb skeletal muscle weight ( P < 0.05, 0.01 and 0.05, respectively). Apelin expression in GA muscle was significantly decreased ( P < 0.05) and elabela, another Apj endogenous ligand, tended to show a non‐significant decrease at 12 weeks after nephrectomy. Administration of AST‐120 inhibited the decline of muscle weight and increase of atrogin‐1 and myostatin expression. Apelin and elabela expression was slightly improved by AST‐120 administration but Apj expression was not, suggesting the involvement of uraemic toxins in endogenous Apj ligand expression. The administration of apelin at 1.0 μmol/kg for 4 weeks to CKD mice suppressed the increase of atrogin‐1 and myostatin, increased apelin and Apj mRNA expression at 30 min after apelin administration and significantly ameliorated weight loss and a decrease of the cross‐sectional area of hindlimb skeletal muscle. Conclusions: This study demonstrated for the first time the association of the Apj endogenous ligand–uraemic toxin axis with skeletal muscle atrophy in CKD and the utility of therapeutic targeting of the apelin–Apj system.